Exploring how stay-at-home orders during the COVID-19 pandemic impedes engagement along the HIV/AIDS care continuum in public hospitals of Southwest Ethiopia: a qualitative study - Gizaw, Abraham Tamirat; Abayneh, Mengistu (Frontiers in Public Health, 2024)
Introduction COVID-19 has rapidly spread across the world. In March 2020, shortly after the first confirmed case of COVID-19 in Ethiopia in March 2020, the government of Ethiopia took several measures. Purpose This study aims to explore how stay-at-home orders during the COVID-19 pandemic hinder engagement with HIV/AIDS care in public hospitals in Southwest Ethiopia. Additionally, we aim to explore the psychosocial challenges faced in accessing services during stay-at-home orders. Methods A descriptive qualitative study was conducted from 20 May to 3 June 2020, using semi-structured, in-depth interviews. In total, 27 study participants were recruited from purposively selected people living with HIV/AIDS (PLWHA) who had experienced delays, declines, or discontinuation of care after COVID-19 was confirmed in Ethiopia on 13 March 2020. The participants were interviewed over the phone and their responses were audio-recorded. Data were transcribed verbatim, translated, and analyzed using inductive thematic analysis in the Atlas ti.7.1 software package. Results The main themes and sub-themes that emerged were psychosocial issues (such as depression, hopelessness, and fear), risk perception (including high risk, susceptibility, and severity), forceful enforcement of stay-at-home orders (such as police beatings, community leaders disgracing, and influence of families and relatives), socioeconomic factors (such as stigma, religion, and transportation costs), misinformation about COVID-19 (such as lockdowns and ART stock-outs), and healthcare factors (such as inadequate health information and long distances to healthcare facilities). Conclusion Overall, these findings were similar to the challenges experienced by PLWHA in adhering to the recommended continuum of care. However, there are additional factors due to COVID-19, such as misinformation and the forceful implementation of the stay-at-home-orders, that impede the continuum of care. Therefore, it is important to strengthen information, education, and communication.